2012
DOI: 10.1002/jbmr.1664
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fragility and structural redundancy

Abstract: The mechanisms of age-related vertebral fragility remain unclear, but may be related to the degree of “structural redundancy” of the vertebra, that is, its ability to safely redistribute stress internally after local trabecular failure from an isolated mechanical overload. To better understand this issue, we performed biomechanical testing and nonlinear micro-CT-based finite element analysis on 12 elderly human thoracic ninth vertebral bodies (ages 76.9 ± 10.8 years). After experimentally overloading the verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 59 publications
6
25
0
Order By: Relevance
“…Results of the FE analysis revealed that also the stresses and strains during compression were in the midrange of values found throughout the vertebra while the model did not predict fracture for this element in most cases. This is in agreement with results of micro-FE analyses recently presented by others which also suggest that failure does not accumulate at the vertebral center but rather near the endplates [35]. Taken together, these results indicate that the particular location at the center of vertebra may be a good predictor mainly because of the consistent correlation between BV/TV and bone strength, and not because it is the weakest link during loading.…”
Section: Discussionsupporting
confidence: 92%
“…Results of the FE analysis revealed that also the stresses and strains during compression were in the midrange of values found throughout the vertebra while the model did not predict fracture for this element in most cases. This is in agreement with results of micro-FE analyses recently presented by others which also suggest that failure does not accumulate at the vertebral center but rather near the endplates [35]. Taken together, these results indicate that the particular location at the center of vertebra may be a good predictor mainly because of the consistent correlation between BV/TV and bone strength, and not because it is the weakest link during loading.…”
Section: Discussionsupporting
confidence: 92%
“…The apparent elastic moduli in the longitudinal direction (Ef) and the transverse directions (E2, £), E2>Ei) were computed and three mechanical anisotropy ratios (EfiEx, E3/E2, E qJ E i ) were defined for each specimen. This material model has been used in various previous studies [27][28][29] and was directly validated against experiments for uniaxial strength behavior (R2 = 0.96, Y = X type of agreement, n = 22 specimens of human bone) [27], To describe the complete multiaxial failure behavior for each specimen, a series of nonlinear finite element simulations was per formed, spanning the 6D multiaxial yield surface. A trans versely isotropic material property set for each specimen was defined by assigning equal moduli in the two transverse direc tions.…”
Section: Methodsmentioning
confidence: 99%
“…A trans versely isotropic material property set for each specimen was defined by assigning equal moduli in the two transverse direc tions. All finite element analyses were per formed using a highly scalable parallel finite element framework, Olympus as described in the previous studies [27][28][29]. For all specimens, all elements in each finite element model were assigned the same isotropic material properties for the solid bone tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a 3D approach was introduced to segment a trabecular network into vertical and horizontal trabeculae of the vertebral body [37][38][39] . Fields et al [37,38] found that vertical trabeculae played a particular important role for the compressive bone strength of vertebrae with low BMD and presumed that vertebral bone strength is better explained by the vertical trabecular bone volume fraction alone, than by the total trabecular bone volume fraction. The scanning electron microscopic images confirmed that the horizontal trabeculae were thinner, whereas the vertical ones were relatively thicker ( Figure 3B).…”
Section: Vertebramentioning
confidence: 99%